Revolutionizing The Inmate Assignment to Correctional Institutions at PADOC. - SHAHABSAFA, MOHAMMAD; TERLAKY, TAMÁS; SHARMA, ANSHUL; BUCKLEN, KRISTOFER BRET (Corrections Today)
The article highlights the project, Inmate Assignment Decision Support System (IADSS). Topics include the issue of the Pennsylvania Department of Corrections (PADOC) regarding the management of the beds at the State Correctional Institutions (SCIs) and optimization of the assignment of the inmates to SCIs; and the involvement of the Lehigh University; and the inmate assignment problem which include psychological, custody-level, and treatment-program availability.